Neighborhood and physical activities of Portuguese adolescents - Santos Maria M; Matos Margarida G; Loureiro Nuno; Mota Jorge; Diniz José A (BMC, 2010)
Abstract Background This study examines associations between perceptions of neighbourhood environment and physical activity and sports within Portuguese adolescents. Methods The sample consisted of 4,877 individuals of both genders, with an average age of 14 years. The instrument used was the Health Behavior School-aged Children questionnaire. Results Perceptions of the neighbourhood being unsafe for children to play and having no place to spend leisure time were associated with lower levels of exercise among adolescents. The perceptions of the neighbourhood being unsafe for children to play (OR = 1.3, p < .005) and the fact of not having a place to spend leisure time (OR = 1.3, p < .005) p < .005) were associated with lower levels of exercise among adolescents. The perception of these variables is associated to a lower probability of exercising. The neighbourhood characteristics are more important to the practice of outdoor sports than of indoor sports. Conclusion The perceptions of the neighbourhood may influence adolescent's physical activity and sports, in different ways.